2013
DOI: 10.1097/ico.0b013e3182a966b4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preoperative Donor Tissue Characteristics on Graft Dislocation Rate After Descemet Stripping Automated Endothelial Keratoplasty

Abstract: PURPOSE To determine the influence of pre-operative donor tissue characteristics on the graft dislocation rate after Descemet’s stripping automated endothelial keratoplasty (DSAEK). METHODS We retrospectively analyzed associations between donor tissue characteristics and graft dislocation rates for consecutive DSAEK surgeries performed in a four year period at a single institution. RESULTS From June 2007 to June 2011, 64 (18%) of 355 eyes underwent a procedure for graft dislocation. There were no differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In fact, there appears to be a dose-response effect for degree of detachment on graft success: grafts that were totally detached conferred an 11-fold increased risk of graft failure, grafts that were attached but required repositioning conferred about a 6-fold increased risk, and partially detached grafts had ~3-fold increased risk of graft failure compared to donors that were not totally or partially detached, or decentered requiring additional surgical intervention. Our findings are similar to those of Hood et al 17 who reported that DSAEK lenticule dislocation was associated with a higher rate of repeat transplantation. We also found that graft dislocation, but not grafts that were partially detached with interface fluid, detrimentally impacted ECD in clear grafts 3 years after surgery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In fact, there appears to be a dose-response effect for degree of detachment on graft success: grafts that were totally detached conferred an 11-fold increased risk of graft failure, grafts that were attached but required repositioning conferred about a 6-fold increased risk, and partially detached grafts had ~3-fold increased risk of graft failure compared to donors that were not totally or partially detached, or decentered requiring additional surgical intervention. Our findings are similar to those of Hood et al 17 who reported that DSAEK lenticule dislocation was associated with a higher rate of repeat transplantation. We also found that graft dislocation, but not grafts that were partially detached with interface fluid, detrimentally impacted ECD in clear grafts 3 years after surgery.…”
Section: Discussionsupporting
confidence: 92%
“…2,[13][14][15][16] Donor characteristics that have not been shown to increase the risk for graft dislocation include donor age, death to surgery time, donor lenticule thickness, and post-processing ECD. 14,17 Additionally, recipient characteristics including preoperative corneal thickness, preoperative diagnosis, history of glaucoma or prior glaucoma surgery, 10 and concurrent cataract surgery have not been associated with an increased incidence of graft dislocation. 17 However, other recipient factors such as older age, 17 aphakia, 18,19 presence of an anterior chamber intraocular lens, 18 postoperative hypotony in eyes with prior glaucoma surgery, 15 previous vitrectomy, 20 and concurrent IOL exchange 18 have been associated with graft dislocation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the three aspects, we suppose the most important and challenging aspect is to prepare the grafts. Some authors analyzed the histopathologic features of the failed DSAEK grafts in human and found thick and irregular grafts were more likely to detach from the posterior stromal bed . Considering that, we hired double‐pass rather than single‐pass technique to harvest an appropriate thickness .…”
Section: Discussionmentioning
confidence: 98%